Accurate reporting of expected delivery date by mothers 9 months after birth. - Poulsen, G; Kurinczuk, J; Wolke, D; Boyle, E; Field, D; Alfirevic, Z; Quigley, M (2011)
OBJECTIVE: To measure agreement between gestational age based on maternal report of expected date of delivery (EDD) 9 months after birth and gestational age at birth in routine hospital data. Furthermore, to examine whether sociodemographic and perinatal factors influenced agreement and whether disagreement affected classification of infants in preterm groups. STUDY DESIGN AND SETTING: The study used data on 8,058 singleton infants from the UK Millennium Cohort Study. Women were interviewed 9 months after birth and interviews were linked to routine hospital data. The infant's date of birth and EDD were used to calculate gestational age in completed weeks. RESULTS: Agreement between maternal report and hospital data was 72% for exact number of weeks' gestation and 94% for agreement within 1 week. Disagreement was associated with the infant not being firstborn, unplanned pregnancy, late or no antenatal care, and low socioeconomic status. Maternal report of gestational age resulted in slightly more children being classified as preterm (6.4%) than gestational age based on hospital data (6.1%). Agreement was found to be poor for postterm births. CONCLUSION: Gestational age based on retrospective maternal reporting of EDD is reliable within 1 week or when used to assign infants to broad gestational groups.